2018
DOI: 10.2196/jmir.7940
|View full text |Cite
|
Sign up to set email alerts
|

Using Plain Language and Adding Communication Technology to an Existing Health-Related Questionnaire to Help Generate Accurate Information: Qualitative Study

Abstract: BackgroundLow-educated patients are disadvantaged in using questionnaires within the health care setting because most health-related questionnaires do not take the educational background of patients into account. The Dutch Talking Touch Screen Questionnaire (DTTSQ) was developed in an attempt to meet the needs of low-educated patients by using plain language and adding communication technology to an existing paper-based questionnaire. For physical therapists to use the DTTSQ as part of their intake procedure, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…49 Health literacy is key in producing accurate information about a patient's knowledge, attitudes and perceptions, but less educated patients face struggles filling out medical questionnaires. 50 This limitation was partially circumvented by using standardised interviewer administered language questionnaires in English, Mandarin, Malay or Tamil, but many were excluded due to their inability to understand the questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…49 Health literacy is key in producing accurate information about a patient's knowledge, attitudes and perceptions, but less educated patients face struggles filling out medical questionnaires. 50 This limitation was partially circumvented by using standardised interviewer administered language questionnaires in English, Mandarin, Malay or Tamil, but many were excluded due to their inability to understand the questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…During further development of the DTTSQ, both the results of this study and the study on response process of the DTTSQ [36] should be taken into account simultaneously. The usability and the response processes will have to be retested in exactly the same manner after adjustments in the DTTSQ have been made.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected in the same study population and at the same time as the data reported in a paper earlier published by Welbie et al [36]. Recruitment took place in 11 primary care practices in deprived areas of Utrecht, The Netherlands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before its official launch, the questionnaire underwent three rounds of optimization following pre-testing with 50 samples [47]. The questions in the questionnaire are concise and easy to understand, which facilitates successful responses from both lay and less educated groups [48]. Throughout this process, the feedback of Shanghai residents was thoroughly considered to refine the questionnaire, ensuring its questions closely mirrored real-life circumstances and were easily comprehensible [49].…”
Section: Survey Instruments and Proceduresmentioning
confidence: 99%